2019
DOI: 10.1371/journal.pone.0213130
|View full text |Cite
|
Sign up to set email alerts
|

The oncoprotein DEK affects the outcome of PARP1/2 inhibition during mild replication stress

Abstract: DNA replication stress is a major source of genomic instability and is closely linked to tumor formation and progression. Poly(ADP-ribose)polymerases1/2 (PARP1/2) enzymes are activated in response to replication stress resulting in poly(ADP-ribose) (PAR) synthesis. PARylation plays an important role in the remodelling and repair of impaired replication forks, providing a rationale for targeting highly replicative cancer cells with PARP1/2 inhibitors. The human oncoprotein DEK is a unique, non-histone chromatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 73 publications
5
15
0
Order By: Relevance
“…This approach allowed us to quantitatively compare the DEK pattern in MCF10A and MDAMB231 cells, representing the normal-like breast basal epithelial cells and triple negative, metastatic basal breast cancer cells, respectively. Previous studies indicate that DEK protein locates mostly within the cell nucleus (4,10,18), and, more precisely, it can be associated with euchromatin (i.e., the active compartments of chromatin) (19). Considering the overexpression of DEK in breast cancer samples, we speculated that its nanoscale organization would differ if compared to normal-like cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach allowed us to quantitatively compare the DEK pattern in MCF10A and MDAMB231 cells, representing the normal-like breast basal epithelial cells and triple negative, metastatic basal breast cancer cells, respectively. Previous studies indicate that DEK protein locates mostly within the cell nucleus (4,10,18), and, more precisely, it can be associated with euchromatin (i.e., the active compartments of chromatin) (19). Considering the overexpression of DEK in breast cancer samples, we speculated that its nanoscale organization would differ if compared to normal-like cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the DEK protein is overexpressed in highly proliferating cells (38), such as cancer cells, and can alter the chromatin topology (7). Our recent study using super-resolution techniques suggested that the commonly observed dispersed nuclear DEK pattern (18,31) is composed of nanoclusters (10). In this work, we investigated the nanoscale characteristics of such clusters in normal-like and aggressive type of breast cancer cell lines to study if DEK’s overexpression correlates with its cluster features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of the DEK oncoprotein with PAR also turns out to be dependent on the polymer length. DEK is involved in various intracellular processes: replication [ 87 , 88 ], DNA repair [ 89 ], RNA processing [ 90 ], and transcription regulation [ 91 , 92 , 93 ]. High DEK levels were shown to contribute to cell immortalization, as well as suppress aging and apoptosis [ 94 , 95 ].…”
Section: Principles Of Par Code Functioningmentioning
confidence: 99%